Implementation of Recitations, Purification, and Teaching Concepts in Increasing Students’ Spirituality and Character at PPI Nurul Burhan Bondowoso - Khumaidah, Sofkhatin; Wasik, Abdul (International Journal of Islamicate Social Studies, 2023)
The concept of recitation, purification, teachings taught by the Koran in Surat al-Jumu'ah: 2 is an effective way in the teaching and learning process and can even create the Tridharma of Islamic Boarding Schools, namely fostering faith and piety to Allah SWT, developing science and expertise useful, as well as devotion to religion, society, and the country. These three concepts became the brainchild of KH. Imam Barmawi in improving the spirituality of his students at PPI Nurul Burhan, Badean, Bondowoso. This study uses a qualitative approach. Methods of data collection using interviews, observation, and documentation. The analysis technique uses the descriptive analysis model of Miles and Huberman. While the data validity technique uses data validity with source and time triangulation techniques. The results of this study indicate that the three concepts are applied at PPI Nurul Burhan; (1) the concept of recitations is applied by reading and writing the translation of the Koran using the Yanbu'a method and the Tarjamah Tafsiriyah study of the Koran with the aim that the students are not only able to read and write the Koran but also able to understand its meaning; (2) the concept of purification is applied by continuing congregational prayers, reciting Shalawat Burdah, and cleaning the pesantren environment. The concept of teaching is implemented with worship workshop activities so that it has a positive effect on the character in terms of piety and cleanliness of the students.